PENGARUH PERILAKU INDIVIDU WAJIB PAJAK ORANG PRIBADI TERHADAP PENGGUNAAN E-FILING DI KOTA MANADO - Kolompoy, Calvin; Ilat, Ventje; Sabijono, Harijanto (ACCOUNTABILITY, 2015)
Tax is one of the main sources of revenue in Indonesia beside sources of petroleum and natural gas which are important for the survival of the nation of Indonesia. Therefore, the government develops a new system to help taxpayer paying their taxes. The purpose of this research is to analyze the influence of individual taxpayer behaviors towards the usage of e-filing in manado city. The analyzing method used in this research is explanative, that is explaining the influence of each of the research variable based on the questionnaire data that has been processed.The result showed that Perceived Usefulness and Perceived Ease of Use give positives influence towards the usage of e-filing, while Behavioral Intention did not bring positive influence towards the usage of e-filing. The Directorate General of Taxation should be more socializing the e-filing program more actively, also the taxpayer should be more open towards the development of taxes technology